On Buddhist ideological trends as reflected in statues from Song dynasty cave shrines. Issue 2 (3rd April 2018) - Li, Jingjie
ABSTRACT: Centrally distributed in the North of Shaanxi 陕西, at Dazu 大足 in Chongqing 重庆, and at Anyue 安岳 in Sichuan 四川, large scale grottoes from the Song dynasty – and the Buddhist statuary found therein – accurately reflect trends in Buddhist ideology of the period. First, filial piety receives greater emphasis. These images even suggest that filial piety is an important component of the practice of the bodhisattva (Skt. bodhisattva-caryā). Scondly, the notion of bodhisattva-caryā was again popularized with greater intensity (during the period). Third, the stone carvings in Dazu from the Northern and Southern Song Dynasties in which Buddhist, Daoist, and Confucian elements are group together reconstruct the then-popular syncretic approach these three traditions. Lastly, buddha traids found in several Northern Song dynasty cave shrines in Shaanxi suggest a continuation of a belief in rebirth in the Pure Land that began in the Tang period.